Antiretroviral Spermicide WHI-07 Prevents Vaginal and Rectal Transmission of Feline Immunodeficiency Virus in Domestic Cats - D'Cruz, Osmond J. (American Society for Microbiology, 2004)
WHI-07 [5-bromo-6-methoxy-5,6-dihydro-3′-azidothymidine-5′-(p-bromophenyl)-methoxy alaninyl phosphate] is a novel dual-function aryl phosphate derivative of zidovudine with potent anti-human immunodeficiency virus (HIV) and spermicidal activities. WHI-07 was active against the feline immunodeficiency virus (FIV). This study evaluated whether topical application of WHI-07 as a single agent and in combination with an organometallic vanadium complex, vanadocene dithiocarbamate (VDDTC), via a nontoxic gel microemulsion can block vaginal as well as rectal transmission of feline AIDS (FAIDS) by chronically FIV-infected feline T cells in the natural host model. Genital transmission of FIV was monitored in recipient cats by the appearance of viral antibodies to FIV Gag proteins and by virus isolation of blood leukocytes as measured by FIV reverse transcriptase activity and FIV-specific PCR. Microbicidal activity was considered effective when the treated cats did not show evidence of FIV infection for up to 18 weeks postchallenge. An aggregate analysis of 46 specific-pathogen-free cats revealed that a single dose of the infected cell inoculum efficiently transmitted FIV infection when delivered into the vagina (100%) or rectum (66%). Pretreatment of the vagina or rectum with 2% WHI-07 alone or in combination with 0.25% VDDTC significantly (P = 0.004) protected cats from genital transmission by the highly infectious inoculum (7 million FIV(Bangston)-infected feline T cells). Collectively, using the vaginal and rectal transmucosal model for FAIDS, our studies demonstrated that WHI-07 either alone or in combination with a vanadocene has clinical potential for the development of a dual-function anti-HIV microbicide for sexually active women.